Construction of Comprehensive Hydrological and Meteorological Drought Index Based on Base Flow and Precipitation and Its Application in Weihe River - FAN Jingjing; SUN Xue; ZHOU Bin; LIU Dengfeng; LIU Chun; LIN Shuai; LI Yunyun (Renmin Zhujiang)
To respond to the national strategy of ecological protection in the Yellow River Basin ,we make a comprehensive assessment of drought in this basin.According to the meteorological data of 20 meteorological stations in Weihe River from 1960 to 2010 and the hydrological data from Huaxian Hydrological Station,the base flow data are obtained by digital filtering,and a new comprehensive drought index related to basic flow and precipitation,i.e.,the comprehensive precipitation and base flow index (CPBI),is constructed by the Copula function.Then,the applicability of CPBI is discussed,and the drought characteristics of the Weihe River Basin are analyzed by this index.The results reveal that CPBI can capture both meteorological and hydrological drought events and comprehensively characterize their drought characteristics;CPBI has a downward trend on all scales,which indicates the drought is becoming more serious;upon the identification by the theory of runs,CPBI can more accurately reflect the severe drought situation of the Huaxian station of Weihe River and can better provide early drought warning;CPBI has variations,and the variation points on seasonal and annual scales are 1994,1993,1985,1999,and 1975.In conclusion,CPBI is an effective drought monitoring index for Weihe River and can provide a reference for early drought warning and response efforts in Weihe River.